Efeito de uma espécie de planta invasora na diversidade de aves em áreas úmidas - Souza, Felipe de Sá Palis e (2014)
The biological diversity can be represented by the abundance and species richness and by the change in the composition between places and environmental gradients. This change can be associated with the conditions and resources offered by the environment. Several factors determine the patterns of species distribution at local and regional level. In Wetlands, the dynamics of flood and drought, together with the different types of hábitats, affect bird´s distribution. In addition, some plant species can also benefit with the dynamic of floods, as the cambara (Vochysia divergens Pohl), known by the great ability of invasion and expansion and by forming monodominant environments with arboreal stratum considered, called cambarazais. This overgrowth, common in several regions, is called encroachment, being responsible for the conversion of fields and savannas in shrub vegetation. In this study it was evaluated the effect of cambarazais on the structure of bird assemblies and how this hábitat contributes in maintaining regional diversity of this group. The work was carried out in the region of the Pirizal, located in the sub-region of the Pantanal of Poconé. The data were collected in grid research of Pirizal, which features 30 plots with different environments: “cambarazal”, “landizal”, “cordilheiras”, “campos de murundus” and exotic fields. For the bird sampling were used two methods, mist nets and census by points. The environmental variables used were the density of cambaras, richness and plant composition and the duration of flooding on the plots. For data analysis we have made simple linear regressions between richness, abundance or composition of birds (represented by one dimension of NMDS) and environmental variables (first axis of the PCA, composed by density of cambaras, plant species richness and flooding duration). To assess whether the patterns found were due to degree of proximity between the plots, it was carried out a Partial Mantel test, with the biological distance in function of environmental and geographic distance. For the second objective, was performed a Permanova to check if there is any difference in bird composition among the different environments. In addition, we simulate as gradual increases of patches of cambarazais affect the bird diversity in landscape. We recorded 183 species of birds in cambarazais distributed in 45 families. The result of the first regression showed that the species richness increased with the change in environmental variables, especially in places with higher densities of cambaras which were more time flooded. In other words, the encroachment has had positive impacts on bird richness. The composition was also affected by environmental variables. The result of Partial Mantel test showed that there was no effect of geographic distance on the bird species composition. The results of the Permanova and simulation showed that the composition was different between different environments and that the cambarazais contribute very much to the bird diversity. The change in the characteristics of the hábitat occurs even in small scales and is determinant for the species distribution. Hábitats with different structures have higher chances of presenting different communities also, what actually contributes to the increasing of regional diversity. The contribution of cambarazais is not only in terms of increasing diversity; it also represents an additional and important environment for several species in the region. Thus, the process of encroachment of cambara, for this studied region, is an important phenomenon for the bird diversity.